MENINGKATKAN KETERAMPILAN MENDENGAR UNTUK MEMBANGUN KOMUNIKASI INTERPERSONAL YANG EFEKTIF BAGI PELATIH SENI AYODYA PALA - Ambarsari, Dewi (Batara Wisnu : Indonesian Journal of Community Services, 2025)
In the context of interpersonal communication, good listening skills are essential for building effective relationships between coaches and students. Although effective communication involves the exchange of information, problems often arise from a lack of listening skills. Through the designed training, participants are taught about the principles of active listening, including mindfulness, empathy, and constructive feedback. This Community Service activity aims to improve listening skills for art trainers at Ayodya Pala Art Center, located in Depok city. This activity is carried out in the form of interactive workshops that include simulations and role-playing, as well as continuous evaluation to measure the improvement of listening skills. The results of this Community Service activity show that the interactive approach is able to improve listening skills, create an inclusive learning environment, and support the preservation of traditional cultural arts. Scientific publications and documentation of activities are additional outputs produced.